(untitled) (Acta Scientiarum. Health Sciences, 2022)
Maintaining a functional natural dentition plays an important role in keeping a satisfactory nutritional status. The aim of this study was to evaluate the relationship between oral health conditions determined by the presence of edentulism and the number of missing teeth, nutritional status and consumption of nutrients by the elderly. This cross-sectional study comprised 494 independent elderly of both genders, over 60 years of age, registered at the Brazilian public health service in Londrina, southern Brazil. The data collection included: oral examinations; anthropometric measurements by calculating the Body Mass Index (BMI); analysis of food consumption based on a multiple pass 24-hour dietary recall and a food intake frequency questionnaire; and structured interviews to obtain sociodemographic information. Multiple linear regression, the Fisher’s Exact test, chi-square and Mannâ€‘Whitney tests, were applied at a 5% significance level. The prevalence of edentulism was 47.3%; this predominated in females, age group from 65 to 74 years, low education level and low/medium economic classification. A larger number of underweight and fewer number of overweight elderly were recorded among the edentulous versus dentate participants (< 0.0001). Significantly lower consumption of several nutrients, as well as fruit, was recorded among the edentulous group. In particular, carbohydrates, vitamins (B1, B9 and C), and the majority of the minerals studied were associated with a larger number of missing teeth. In conclusion, tooth loss was associated with the food consumption pattern of some macro- and micronutrients and the nutritional status of the Brazilian elderly.